APPLICATION PERFORMANCE ASSESSMENT WORK USING SIMPLE ADDITIVE WEIGHTING (SAW) METHOD - Tias Ambarwati; Fajar Masya (Jurnal Riset Informatika, 2020)
Handling Infrastructure and Public Facilities (PPSU) are officers formed in 2015 by Basuki Tjahaja Purnama, the Governor of DKI Jakarta at the Kelurahan level. The assessment carried out by Munjul Kelurahan is currently still subjectively subject to a section by the Head of the Economy and Development Section and there are no clear and detailed parameters in determining workers' assessments. So that it can result in non-transparent PPSU performance evaluation The application of decision support systems in the assessment of PPSU work performance will provide a structured assessment. One method that can be used in decision support systems is Simple Additive Weighting (SAW). The concept of this method is to look for a performance rating (priority scale) on each alternative in all attributes. The calculation can determine the best PPSU accurately to make PPSU recruitment decisions every year.